Enhancing Speaking Skills of EFL Students Through Debate - Cut Nurhalizah Aziz (Journal of English Education, Literature and Linguistics, 2020)
The purpose of this study was to find out whether or not using debate improved the students’ speaking skill achievements and how much debate contributed to each aspect of speaking skills. This was a qualitative research design as an action study. Eleven students Faculty of English Teaching semester 5 completed the survey. The data was collected through a survey questionnaire as the data collection technique, including Yes or No questions and one statement question. Overall, the students believed that the debate was a good learning activity. The data of this study are all activities in the teaching and learning process related to the focus of study in the field of speaking skills related to EFL students, while the teaching and learning process as an integrated writing implementation as a data source. The respondents believed that the debates helped improve and build courage for their speaking skills. In addition, as the students claim, other benefits of the debates included build courage with a spontaneous argument, boosting confidence, have a new vocab, and learn how to thinking in a critical way.